EVALUASI PEMBELAJARAN BERBASIS E-LEARNING PADA MAHASISWA DI SEKOLAH TINGGI ILMU KESEHATAN - Putu Windi Ridayanti; Kadek Devy Marleni (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
The current learning process mostly uses a blended learning system. Students can study in class and even study online using a learning management system (LMS). The purpose of this research is to evaluate a program which evaluates learning using elearning. The research method is descriptive, where the research assesses input (lecturers, staff and students), learning process (elearning readiness, learning equipment readiness and preparation of RPS) then output (satisfaction, evaluation and student grades). The results of the research found that in terms of lecturer human resources, 82.8% of lecturers had prepared learning devices for their respective elearning courses and as many as 5% of students complained about the problem of not being able to access elearning due to signal difficulties. In terms of the process, there are still lecturers who have not prepared complete learning tools. Meanwhile, in terms of output, students get good grades because the assignments are complete, the material reads well. The conclusion is that overall the use of LMS in the learning process is very helpful and can improve abilities and achieve learning outcomes easily. Although there are still obstacles from the lecturer and student side.